The marine fauna of New Zealand : Cephalopoda : Oegopsida Architeuthidae (giant squid) - Forch, Ellen Celia (Wellington National Institute of Water and Atmospheric Research, 1998)
NIWA Biodiversity Memoir #115
Keywords: Marine fauna; New species; Life cycle; Ophiuroidea; Giant squids